The Bank's Act of Placing a Debt-Defaulter Sticker on the Aggrieved Party - Rahmatika, Rizka; Cholil, Mochamad (LEGAL BRIEF, 2025)
This research investigates the unilateral action of banks placing "default debtor" stickers on properties, even when the targeted party is not a debtor, causing both material and immaterial harm. The study aims to analyze the legal protection available to affected parties and determine the bank’s liability for such actions. A normative legal research method is used, employing statutory, case, and conceptual approaches. Data is analyzed prescriptively to develop legal arguments based on existing laws. The findings indicate that such actions when conducted without lawful basis or proper verification can constitute unlawful conduct under Article 1365 of the Indonesian Civil Code and violate banking secrecy and consumer protection principles. As institutions of trust, banks are held liable for damages caused by procedural negligence, including when carried out by third parties such as debt collectors. The study concludes that stricter legal mechanisms are necessary to prevent such harmful practices. These mechanisms should include internal safeguards through bank SOPs and external supervision by the Financial Services Authority (OJK). Strengthening these legal protections is essential to uphold justice and ensure that consumers of banking services are treated fairly and their rights respected within the financial sector